To meditate the Torah in the history and the history from the Torah: Intertextual-canonical reading of Ps 1 and 2 (I) - Astorga Guerra, Pedro (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The present article is a study of Ps 1 and 2 from an intertextual-canonical reading. A reading of this kind demands principally a literary study of both Psalms to see if they contain some intertextual links that put them in mutual relation. Secondly, combining the intertextual reading with the canonical reading, the question arises for the function of these Psalms placed to the beginning of the Psalter for the interpretation of the same one. Finally, Ps 1 and 2 also have relation with other relevant texts of the Old Testament canon, making possible a more wide understanding of those. In the second report of this article we will study the reception and interpretation that these two Psalms have had in the New Testament.
Keywords: intertextual links; meditation; Torah; just; king